Impact of the positive deviance approach on breastfeeding practices among tribal pregnant women: A before - After intervention study - Abhay Srivastava; Kanchan Gwande; Sudip Bhattacharya; Vijay Kumar Singh (Wolters Kluwer Medknow Publications, 2019)
Introduction: Breastfeeding is very important for the infant and for the mother. Breastfeeding practices in India and abroad are not up to the mark, and they pose serious health risk to the mothers and the babies. Methodology: This single-group before-after intervention study was conducted to assess the impact of positive deviance (PD) approach on knowledge about exclusive breastfeeding (EBF) practices among tribal pregnant women. The sample size was 376. Data were collected using convenient sampling method. At first, we identified eight positive deviants from that area. They were trained by the investigator regarding EBF practices. They were also motivated to share their knowledge and practices in the community. Results: It was observed that knowledge regarding initiation of breastfeeding (<1 h of birth) increased from 181 (52.2%) to (67.1%) among 347 study participants. Only 81 (23.3%) knew that breastfeeding should be on demand before intervention, which increased by 21% after the intervention. The majority of the study participants, i.e., 286 (82.4%) knew the advantages of breast milk. The proportion of study participants who knew that breastfeeding should not be stopped during mother's illness was 171 (49.3%) before and 229 (66%) after intervention. Before intervention, around one-fourth, that is, 85 (24.5%), knew that if the mother is not producing enough milk, then she should visit a health center which increased to 130 (37.5%) after intervention. The majority of the participants, i.e., 145 (41.8%) knew that bottle feeding should not be done for the babies which increased in proportion to around 55% after intervention. A statistically significant (P < 0.001) increase in knowledge was observed. Conclusion: It is possible to increase the awareness and practice level among the lactating mothers for EBF using the positive deviant approach. Recommendation: The concept of PD approach can be further popularized as they can strengthen our existing health system for better health outcomes in future.